Assessing Construction Accident Costs and Influencing Factors in Eastern Province, Saudi Arabia - Alotaibi, Abdulaziz; Tamrin, Shamsul Bahri Hj. Mohd; Guan, Ng Yee; Hassanain, Mohammad (Advances in Social Sciences Research Journal, 2025)
The construction sector in Saudi Arabia’s Eastern Province is vital for economic growth, yet workplace accidents impose severe human and financial costs. Vision 2030’s industrial expansion highlights the need for accurate assessments of accident-related costs to inform effective safety policies. This study aimed to estimate direct, indirect, and total costs of construction accidents from 2016 to 2021, considering sociodemographic, company, project, and accident characteristics. A retrospective cross-sectional design analyzed 348 randomly selected accident cases reported to the General Organization for Social Insurance (GOSI). Data on direct costs were obtained from GOSI records, while indirect costs were collected through surveys and interviews with company personnel. Descriptive statistics and generalized linear models (GLM) with Gamma distribution were employed to identify cost predictors. The indirect costs averaged SAR 4,018.60, surpassing direct costs of SAR 4,855.60, accounting for approximately 67% of total accident costs. Larger companies (>500 employees) and permanent injuries significantly increased both cost types. Work on scaffolding, rooftops, or ladders was associated with higher expenses. The workforce was predominantly South Asian laborers on medium-sized projects. GLM models effectively predicted accident costs, underscoring company size and injury severity as key determinants. The indirect costs constitute a major component of construction accident expenses in the Eastern Province, often overlooked in traditional safety investments. Tailored interventions focusing on large firms and high-risk work environments are essential to reduce financial burdens and enhance worker safety. This localized cost estimation framework supports evidence-based occupational health and safety policies aligned with Saudi Arabia’s Vision 2030 goals.